Persepsi dan Aktifitas Kader PSN DBD terhadap Pencegahan dan Pemberantasan Demam Berdarah Dengue - Indah Trisnaniyanti, Yayi Suryo Prabandari, Citraningsih Y (Berita Kedokteran Masyarakat (BKM), 2010)
Background: Banjarbaru municipality is a DHF endemic area because of the annual occurrence. From the year of 2001 up to 2007 there was always a number of people who was died because of the disease. Effort to control DHF by municipality health office of Banjarbaru was DHF promotion, early awareness on DHF and forming trained cadre of mosquito net control (PSN) of DHF. This was shown from the result of PJB from the year of 2002 up to 2007 and the average of AJB was under 95% and the incident rate of DHF was still up and down every year. The cadre of PSN DHF was expected could stimulate communities’ participation in order to implement the PSN so that DHF incident could be suppressed.Objective: This research was aimed to find out the correlation of perception and activity of cadre of PSN DHF in DHF prevention and control in Banjarbaru municipality.Methods: This was an observational research that used cross sectional design. The research variable consisted of independent variable that was internal factor (knowledge, age, education level, job) and external factor (information source, information media) and the confounding variable was perception on cadre of PSN DHF and the dependent variable was activity of PSN DHF cadre. The sample was taken with proportional random sampling and the analysis being used was univariate analysis and bivariate analysis with t test and regression linear was used to examine the correlation strength.Results: The research result showed that respondent’s perception was already good (81,08%) and respondent’s activity was also good (77,36%). There was a significant correlation between respondent’s knowledge on DHF disease with perception of PSN DHF cadre (p<0,05) while age, education level and job did not have significant correlation with perception of PSN DHF cadre (p>0,05). There was an unsignificant correlation between analysis of information source and information media with perception of PSN DHF cadre (p>0,05). Furthermore, there was a significant correlation between cadre’s perception with cadre’s activity (p < 0,05).Conclusion: Perception and activity of PSN DHF cadre in the municipality of Banjarbaru was already fine. There was a correlation between internal factor that was knowledge with cadre’s perception, while the other internal factor (age, education level, and job) did not have correlation with perception. External factor (information media and source of information) was not related with perception of PSN DHF cadre. Indeed, there was a correlation between perception and cadre’s activity.Keywords: perception, activity, cadre of PSN DHF